ANALISIS PERBANDINGAN KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI INDONESIA SEBELUM DAN SESUDAH KRISIS EKONOMI GLOBAL 2008 - Ariani, Dinie; Fadli, Fadli; Lismawati, Lismawati (JURNAL FAIRNESS, 2013)
This research aims is to determine whether there are differences between financial performance of local governments in Indonesia at the level of financial independence, financial effectiveness, financial efficiency, and financial activities before and after the global economic crisis 2008. To analyze the financial performance of local governments, the research conducts financial ratio analysis of APBD. The samples used in this research is local governments in the province of DKI Jakarta, East Kalimantan, Riau, East Java, North Sumatra, Riau Islands, South Sumatra, Central Java, South Kalimantan and Lampung, which are the top ten provinces which have the largest foreign trade value according to the Badan Perencanaan dan Pembangunan Nasional (Bappenas) in 2010 and is expected to hit the global economic crisis 2008, and that was published the data of APBD from 2003 to 2012. The analysis instrument used to determine differences between financial performance before and after the global economic crisis of 2008 was the Paired Sample T Test. The results of research show that there were no differences between the financial performance of the local governments in Indonesia at the level of financial independence and financial effectiveness before and after the global economic crisis 2008. In other hand, there are differences between the financial performance of the local governments in Indonesia at the level of financial efficiency and financial activity before and after the global economic crisis 2008.